THE BAUSCHINGER EFFECT AND APPLICATIONS TO THE MANUFACTURE OF HIGH STRENGTH LINEPIPE - Uko, Kaiso Donatus (My University, 1978)
The macroscopic stress-strain characteristics of many common engineering materials embraces several complex phenomena which are generally attributed to the dependence on loading history. Certain particular aspects of this history related behaviour may be classified under the general heading, the Bauschinger Effect. Investigations into the Bauschinger Effect have produced a variety of continuum plasticity models to explain the phenomenon. The models vary in their degree of complexity but even the more sophisticated ones have not always shown good agreement with experimental observations. Microscopic theories have also been proposed to describe the work hardening behaviour of alloys composed of a hard second phase in a plastically deformable matrix. The work of Brown and Stobbs is an example in which the Bauschinger Effect is treated as an integral part of the work hardening phenomenon in a two phase material. This thesis examines three continuum models in some detail in order to determine the role played by internal stresses on the macroscopic behaviour and the Bauschinger Effect. A modification to an existing model is introduced and shown to improve the description of some experimentally determined cyclic stress-strain data. Furthermore, the microscopic model due to the Brown and Stobbs has been studied quantitatively. The original model was proposed based on detailed observations of the plastic deformation of a simple model system of dispersion hardened single crystals of copper-silica. In this present study, an attempt is made to generalize the model to more complex polycrystalline systems comprised of four spheroidized plain carbon steels which contain different volume fractions of Fe₃C type carbides and three linepipe grade HSLA steels, the microstructures of which are relatively more complex. The experimental inputs to the model were determined from reverse flow experiments performed in a well aligned tension - compression loading fixture. The final aspect of the work of this thesis was focused on the study of an industrial application in which the Bauschinger Effect can play a major role. The D-O-E pipe making process was selected for study in this regard. The general objective of the thesis was to provide a better understanding of the Bauschinger Effect in terms of its causes and practical implications in common structural steels. Certain specific conclusions have been reached in this regard.